2023
DOI: 10.3390/f14020395
|View full text |Cite
|
Sign up to set email alerts
|

Working Posture and the Center of Mass Assessment While Starting a Chainsaw: A Case Study among Forestry Workers in Croatia

Abstract: Motor-manual work with a chainsaw is still an irreplaceable occupational activity in forest harvesting operations in Croatia and in many other countries. Chainsaw workers are exposed to different risk factors, such as noise and vibrations, heavy load lifting, awkward and preflexion postures, repetitive movements, etc. The working posture and the assessment of the center of mass plays an important role in understanding the exposure of forest workers to postural and occupational risks, either as a part of the en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 20 publications
2
4
0
Order By: Relevance
“…McGill [36] showed the reduction in shear forces of lumbar spine from 1900 N to 200 N when a person changed from flexed posture to neutral spine posture. The obtained results of flexion of the lower part of the spine are in accordance with the obtained values of Center of Mass vertical deviation [21] and with other findings on postural strain in the spine area To reduce the risk of musculoskeletal disorders, chainsaw workers should be educated in taking the correct position of the upper body, i.e., the rule of hip hinge [38]. For the L3L4 spine area, kinematic data showed flexion of the vertebrae in the "from the ground" method, which deviates to a lesser extent from the N-pose.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…McGill [36] showed the reduction in shear forces of lumbar spine from 1900 N to 200 N when a person changed from flexed posture to neutral spine posture. The obtained results of flexion of the lower part of the spine are in accordance with the obtained values of Center of Mass vertical deviation [21] and with other findings on postural strain in the spine area To reduce the risk of musculoskeletal disorders, chainsaw workers should be educated in taking the correct position of the upper body, i.e., the rule of hip hinge [38]. For the L3L4 spine area, kinematic data showed flexion of the vertebrae in the "from the ground" method, which deviates to a lesser extent from the N-pose.…”
Section: Discussionsupporting
confidence: 89%
“…The application of innovative wearable technology, like a motion capture suit, is increasingly being used in ergonomic research [16,17] and in sports for the investigation of kinematic differences in the technical performance of a certain elements [18,19]. The application of similar technologies for ergonomic research in the forestry sector is more recent, and is mainly related to body posture analysis using the Zephry Bioharness measurement system [20], Center of Mass (CoM) assessments using a motion capture suit [21], and designing a work aid for a chainsaw workers aligned with the solutions of Industry 5.0 [10].…”
Section: Introductionmentioning
confidence: 99%
“…Classification of articles by the risk factor category yielded 157 records in 15 fields (Figure 6). The most represented machines and tools were chainsaw (37), skidder (17), pre-harvesting tools (16), harvester (14), forwarder (12), and farm tractor (12). Overall, almost onethird of all records were noted in Brazilian articles (Figure A2) where the most records were observed for skidder (8), feller buncher (7), harvester (6), pre-harvesting tools (6), chainsaw (5), and forwarder (5).…”
Section: Article Classificationmentioning
confidence: 99%
“…A study by Borz et al [32] in motor-manual felling reported a postural risk index of 191.11% for the worker handling the brush cutter and 192.02% for the manual assistant, indicating rather reduced risks. Starting a chainsaw is a mostly over-looked operation from an ergonomics standpoint; however, Landekić et al [17] stated that the safest method of starting the chainsaw from the ground is the riskiest in terms of postural load, which, over time, can contribute to health problems in forest workers. The results of the Brazilian study [53] showed that the feller buncher operators remained seated in a static position for a long period, with fists turning outside the neutral line and without pauses for recovery, although REBA and RULA (Rapid Upper Limb Assessment) methods identified low postural risk.…”
Section: Postural Loadmentioning
confidence: 99%
“…The location of the CoM of a seated participant can be used for seat design, restraint systems [19], and other human-centered products and environments. Also, its understanding and consideration are important in body stability [20], posture and alignment [21], lifting and manual handling [18,22], and biomechanics [23]. An evaluation of the CoM requires a time-efficient measurement and high accuracy, especially in the case of body balance measurements [20].…”
Section: Introductionmentioning
confidence: 99%